Drug‐induced hypersensitivity syndrome due to minocycline complicated by severe myocarditis. Issue 2 (February 2014) - Kanno, Kyoko; Sakai, Hiroyuki; Yamada, Yutaka; Iizuka, Hajime
Abstract A 60‐year‐old woman presented with a 13‐day history of a generalized erythematous rash accompanied by fever, periorbital edema and axillary lymphadenopathy. Prior to the appearance of the rash, the patient had been treated with intermittent courses of oral minocycline for cystitis. The patient was diagnosed with drug‐induced hypersensitivity syndrome (DIHS) due to minocycline. During the admission, infectious endocarditis was suspected and the patient was treated with i.v. gammaglobulin (0.4 g/kg per day). The following day, the patient suffered from systemic deterioration and symptomatic low blood pressure that prompted repeat echocardiography which revealed an ejection fraction of 10%. DIHS‐associated myocarditis was suspected and management with circulation assistance devices and steroid pulse therapy were started, resulting in satisfactory resolution. A rise in titer of human herpesvirus‐6, cytomegalovirus and Herpes simplex virus‐1 antibodies was detected. Although minocycline‐induced myocarditis is rare, this severe drug reaction should be considered with DIHS.